A Combination of Long-Day Suppressor Genes Contributes to the Northward Expansion of Rice - Cui, Yongxia; Wang, Junrui; Feng, Li; Liu, Sha; Li, Jiaqi; Qiao, Weihua; Song, Yue; Zhang, Zongqiong; Cheng, Yunlian; Zhang, Lifang; Zheng, Xiaoming; Yang, Qingwen (Frontiers in Plant Science, 2020)
Growing cultivated rice with a moderate heading date is the key to expanding its cultivation area and maintaining stable yields. The genes that regulates heading date are largely cloned; however, it remains unclear how genetic mutations and their combinations affect the heading date and adaptability of cultivated rice. Here, we report the analysis of genetic variation in eight long-day flowering suppressor genes (Hd1, DTH8, Ghd7, OsCOL4, DTH7, Hd6, Se5, and PhyB) and the phylogenetic relationship of eight genes. Genetic variations in DTH8, Ghd7, Hd1, DTH7, PhyB and OsCOL4 are correlated with differences in heading date and the correlation between the genetic diversity of Hd6 and Se5 and rice heading data is weak. One group of haplotypes of DTH8, Ghd7, Hd1, DTH7, PhyB, and OsCOL4 are associated with earlier heading dates and appear to have accumulated during the northward expansion of rice cultivation. A minimum of four group A alleles of DTH8, Ghd7, Hd1, DTH7, PhyB and OsCOL4 are required for the growth of cultivated rice at latitudes above 30°N. This study presents a preliminary investigation of the genetic patterns and adaptation mechanisms of long-day flowering suppressor genes and provides a useful reference for the molecular breeding of rice cultivars for various environments and farming systems.